Anaphylaxis in Poland: the epidemiology and direct costs - Jahnz-Rozyk, Karina (Postepy Dermatol Alergol, 2017)
INTRODUCTION: Epidemiological data on anaphylaxis have been underestimated both in Poland and worldwide. AIM: To evaluate the prevalence of anaphylaxis in Poland, including a classification by gender, age and residential region. MATERIAL AND METHODS: The data used in the analysis were derived from two sources, the National Health Fund records of healthcare services for 2008–2015 (official statistics) and a questionnaire-based survey conducted in 2015 on a sample of 305 allergists practicing in different regions of Poland. RESULTS: In 2015, 3144 people received treatment for anaphylactic shock (T78.0, T78.2, T80.5, T88.6) with an estimated prevalence rate of anaphylaxis of 8.2 per 100,000 (8.4 for females and 7.9 for males). The highest prevalence rate was found for women aged 50–54 years (14.5 per 100,000). There was a very large difference in the prevalence of anaphylaxis between rural and urban areas (13.1 vs. 0.8 per 100,000). In 2015, the Polish NHF spent PLN 3.5 million (EUR 835,000) on the management of anaphylaxis. Of the allergists surveyed, 73% had been currently managing patients who had experienced anaphylactic shock. The most common causes of anaphylaxis included insect venom (41.4%), food (29.8%) and drugs (17.4%). CONCLUSIONS: A central anaphylaxis registry should be established in Poland. This is the only approach that would allow collecting a wide range of reliable information on the cases, management and consequences of anaphylaxis. Ongoing management of patients who have experienced anaphylactic shock should be improved.